River‐Ditch Flow Statistical Relationships in a Traditionally Irrigated Valley Near Taos, New Mexico. (11th January 2020) - Cruz, Jose J.; Fernald, Alexander G.; VanLeeuwen, Dawn M.; Guldan, Steven J.; Ochoa, Carlos G.
Abstract: Current and predicted drought and population growth challenge the longevity of irrigation systems of northern New Mexico. Irrigation ditches, also known as acequias, draw runoff directly from rivers without use of storage reservoirs, so it is important to understand the effects of changing river flow on irrigation flow. This study sought to examine river‐ditch relationships in an agricultural valley of the region. A first order linear model was used to fit the river‐ditch flow relationship on which daily river flow was the explanatory variable and daily ditch flow the response variable. A strong positive relationship between river and ditch flow was observed for all but one of the ditches. Using a statistical model approach that addressed serial autocorrelation, heteroscedasticity, as well as outlier observations, statistical evidence at 5% significance level was found in all ditches but one. The ditch without a positive relationship was at a downstream location, subject to upstream flow diversion that may have influenced river‐ditch flow relationships. Results from this study can be used to evaluate the potential effects of changing socioeconomic dynamics and climate change projections in the operations of these irrigation systems to better understand and manage their water resources.